2011
DOI: 10.1007/s11104-011-0995-4
|View full text |Cite
|
Sign up to set email alerts
|

How does drought stress influence the decomposition of plant litter with contrasting quality in a grassland ecosystem?

Abstract: Background and aims Plant litter quality and water availability both control decomposition. The interaction of both parameters was never studied. We used a grassland site, where litter of contrasting quality, i.e. green litter (fresh leaves; high quality) and brown litter (dead leaves, which underwent senescence but which are still attached to the plant; low quality), is returned to soil. Green and brown litter were exposed in the field under regular weather and drought conditions. The objective of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
84
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(97 citation statements)
references
References 44 publications
13
84
0
Order By: Relevance
“…In current study, this was the most probable reason of systematic decline in percentage of P with increasing periods of drought. Besides Liebersbach et al (2004) reported that salinity reduces the availability of P to by reducing the diffusion and mass flow from the soil (Schimel et al, 2007;Sanaullah et al, 2012;Lambers et al, 2008;He and Diskstra, 2014).These statements logically justify the outcomes of current study. Apart from this, Feis also considered as an important micronutrient playing important role in agriculture.…”
Section: Discussionsupporting
confidence: 77%
“…In current study, this was the most probable reason of systematic decline in percentage of P with increasing periods of drought. Besides Liebersbach et al (2004) reported that salinity reduces the availability of P to by reducing the diffusion and mass flow from the soil (Schimel et al, 2007;Sanaullah et al, 2012;Lambers et al, 2008;He and Diskstra, 2014).These statements logically justify the outcomes of current study. Apart from this, Feis also considered as an important micronutrient playing important role in agriculture.…”
Section: Discussionsupporting
confidence: 77%
“…The most common effect of drought is a decrease in soil biological activity, including decreases in soil enzyme activity (Lorenz et al, 2001;Yavitt et al, 2004;Henry et al, 2005;Peñuelas, 2005, 2010;Sardans et al, 2006Sardans et al, , 2008aSardans et al, , 2008d, mineralization (Fig. 1), and SOM decomposition (Van Meeteren et al, 2008;Sanaullah et al, 2012) that frequently decrease the availability of soil nutrients (Fig. 1).…”
Section: Effects On the Availability And Stoichiometry Of Nutrients Amentioning
confidence: 99%
“…The mean annual temperature and precipitation for the period 2006-2010 was 11.2°C and 773 mm, respectively. Details of the experimental site can be found elsewhere [23][24][25][26][27][28][29].…”
Section: Experimental Sitementioning
confidence: 99%